Ascending stair evacuation: walking speed as a function of height. (7th November 2016) - Delin, Mattias; Norén, Johan; Ronchi, Enrico; Kuklane, Kalev; Halder, Amitava; Fridolf, Karl
Summary: There is reason to believe that factors such as physical exertion and behavioural changes will influence the ascending walking speed and ultimately the possibility of satisfactory evacuation. To study these effects, a 2‐year research project was initiated with the focus on effects of physical exertion on walking speeds, physiological performance and behaviours during long ascending evacuations. Two sets of experiments on human performance during ascending long stairs, with a height of 48 and 109 m, were performed. The results include aspects such as walking speeds, physical exertion (oxygen consumption, heart rates and electromyography data), perceived exertion and behavioural changes, showing that physical work capacity affects walking speeds in case of long ascending evacuation and should be considered while using long ascending evacuation. Analysis of both walking and vertical speeds is recommended because it provides additional insights on the impact of stair configuration on vertical displacement and the importance of not using the same value for walking speed for different stairs because the design of the stairs has an impact. The novel datasets presented in this paper are deemed to provide useful information for fire safety engineers both for assisting fire safety design as well as the calibration of evacuation modelling tools. Copyright © 2016 John Wiley & Sons, Ltd.